Addition of Quick lime to the Stabilization of Humbang Hasundutan's Soil Peat Through The California Bearing Ratio Laboratory Test - Suhairiani, Suhairiani; Panjaitan, Nahesson; Keristiana Sinaga, Enny; Zulfa Yuzni, Siti (International Journal of Science, Technology & Management, 2022)
This research is a research on the development and utilization of peat soil material that is often found in the Humbang Hasundutan district, where peat soil that has been stabilized with lime can later become new soil parameter data that can be used for road subgrade construction improvements. The purpose of this study was to stabilize the Humbang Hasundutan peat soil mixed with lime to meet the standards for road subgrade construction, which will be tested with the California Bearing Ratio (CBR). This study used experimental methods carried out in the laboratory, by conducting tests to obtain new soil parameter data by trying variations of 10%, 20% and 30% initial lime. From the results obtained, the results of the CBR test of peat soil with a lime mixture variation of 20% have met the specifications of Highways for road construction subgrade, which is 5.5%.